Speaking Anxiety and Strategies Used by ESL Learners to Overcome in Their Classroom: a Case Study in Management and Science University (MSU) Shah Alam, Malaysia - Shamsuri, Nusrhamira Afiqah Binti Mohd; Anita, Anita; Kamaruddin, Liyana Syahira Binti; Azhan, Nurin Auni Syauqina Binti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This research study aiming at identifying the sources of the ESL studentsâ€™ speaking anxiety in English speaking comprehension and identifying the strategies used by ESL students to overcome speaking anxiety in English class. This research used a qualitative approach that employed a case study and gathrered the information through interviewing 8 undergraduate students from a private university in Shah Alam Malaysia. All the interview questions covered three components, they were communication apprehension, fear of negative evaluation and test anxiety and the strategies that were used by the respondents to overcome their speaking anxiety. The data analysis technique used was descriptive qualitative. As the result, the researcher found that anxiety, commonly felt by most second language learners contributed by some factors that came from the students and also from teachers. Therefore, to deal with these conditions, both teachers and students need to take part in contributing to what they can do to eliminate the speaking anxiety. Since the success of learning language mostly depends on the communication skills that definitely Â requires a lot of effort to make the learning journey meaningful.